Multi-GPUs parallel computation of dendrite growth in forced convection using the phase-field-lattice Boltzmann model - Sakane, Shinji; Takaki, Tomohiro; Rojas, Roberto; Ohno, Munekazu; Shibuta, Yasushi; Shimokawabe, Takashi; Aoki, Takayuki (Journal of crystal growth, 2017)
Melt flow drastically changes dendrite morphology during the solidification of pure metals and alloys. Numerical simulation of dendrite growth in the presence of the melt flow is crucial for the accurate prediction and control of the solidification microstructure. However, accurate simulations are difficult because of the large computational costs required. In this study, we develop a parallel computational scheme using multiple graphics processing units (GPUs) for a very large-scale three-dimensional phase-field-lattice Boltzmann simulation. In the model, a quantitative phase field model, which can accurately simulate the dendrite growth of a dilute binary alloy, and a lattice Boltzmann model to simulate the melt flow are coupled to simulate the dendrite growth in the melt flow. By performing very large-scale simulations using the developed scheme, we demonstrate the applicability of multi-GPUs parallel computation to the systematical large-scale-simulations of dendrite growth with the melt flow. •3D phase-field-lattice Boltzmann model (PFLBM) is developed.•Multi-GPUs parallel computational scheme is developed for the 3D PFLBM model.•Very large-scale simulations of dendrite growth under forced convection are shown.